Q-TWiST analysis of panitumumab plus FOLFOX4 versus FOLFOX4 alone in patients with previously untreated wild-type RAS metastatic colorectal cancer. (3rd March 2016) - Wang, Jianmin; Hechmati, Guy; Dong, Jun; Maglinte, Gregory A.; Barber, Beth; Douillard, Jean-Yves
Abstract: Introduction: Panitumumab plus infusional 5-fluorouracil, leucovorin, and oxaliplatin (FOLFOX4) significantly improved overall survival versus FOLFOX4 alone in patients with previously untreated wild-type RAS metastatic colorectal cancer (mCRC). We applied a quality-adjusted time without symptoms of disease or toxicity (Q-TWiST) analysis to provide an integrated measure of clinical benefit, with the objective of comparing quality-adjusted survival between the two arms. We acknowledge that there are limitations associated with Q-TWIST methodology for crossover trials. Methods: For each treatment arm, the truncated mean times spent in the toxicity (TOX: grade 3 or 4 adverse events), time without symptoms of disease or toxicity (TWiST), and relapse (REL: after disease progression) states were estimated by the product-limit method, and adjusted using utility weights derived from patient-reported EuroQol 5-dimension measures. Sensitivity analyses were performed in which utility weights (varying from 0 to 1) were applied to time in the TOX and REL health states. Results: Quality-adjusted overall survival time was statistically significantly longer with panitumumab plus FOLFOX4 (20.5 months) than with FOLFOX4 alone (18.2 months) ( P = 0.025). Conclusion: In patients with previously untreated wild-type RAS mCRC, panitumumab plus FOLFOX4 significantly improved quality-adjusted survival compared with FOLFOX4 alone.